NIN Is Involved in the Regulation of Arbuscular Mycorrhizal Symbiosis - Guillotin, Bruno; Couzigou, Jean-Malo; Combier, Jean-Philippe (Frontiers in Plant Science, 2016)
Arbuscular mycorrhizal (AM) symbiosis is an intimate and ancient symbiosis found between most of terrestrial plants and fungi from the Glomeromycota family. Later during evolution, the establishment of the nodulation between legume plants and soil bacteria known as rhizobia, involved several genes of the signalling pathway previously implicated for AM symbiosis. For the past years, the identification of the genes belonging to this Common Symbiotic Signalling Pathway have been mostly done on nodulation. Among the different genes already well identified as required for nodulation, we focused our attention on the involvement of Nodule Inception (NIN) in AM symbiosis. We show here that NIN expression is induced during AM symbiosis, and that the Medicago truncatula nin mutant is less colonized than the wild type M. truncatula strain. Moreover, nin mutant displays a defect in the ability to be infected by the fungus Rhizophagus irregularis. This work brings a new evidence of the common genes involved in overlapping signalling pathways of both nodulation and in AM symbiosis.